Hubungan Kegunaan dan Kemudahan Penggunaan SAIBA dengan Kualitas Laporan Keuangan Kantor Wilayah DJP Bali - Prasetyo, Budi Ismanto; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p05, 2018)
The change in the accounting basis from cash to accrual to accrual basis is due to some things that cash-accrual accounting can not meet. The purpose of this research is to know and analyze the relationship of usability and ease of use of Accounting System of Institution Based Accrual (SAIBA) with quality of financial report of Regional Office of DGT Bali. The population in this study are SAIBA operators from all work unit in DGT Bali Regional Office. The sampling technique used was the census. Data analysis techniques used to test the hypothesis in this study is Spearman Rank correlation analysis. The results show that the strength of the relationship of the SAIBA usability variable with the quality of the financial statements can be classified into very strong relationships, as well as the strength of the relationship of the SAIBA ease-of-use variable with the quality of the financial statements. Keywords: Uses SAIBA, Ease of Use SAIBA, Quality of Financial Statement